MENIERE’S DISEASE - Helena Era Millennie; Badrul Munir; Zamroni Afif; Ria Damayanti; Shahdevi Nandar Kurniawan (Journal of Pain, Headache and Vertigo, 2021)
Meniere’s disease is a disorder of the inner ear resulting in symptoms of episodic vertigo, tinnitus, hearing loss and aural pressure. Although the exact etiology is uncertain, it is associated with raised pressure in the endolymph of the inner ear (endolymphatic hydrops). The diagnosis of Meniere's disease is based on the clinical setting of the patient. This disease usually presents with unilateral ear symptoms but can be also bilateral. Meniere's disease attacks are usually random and episodic (approximately 6-11 per year), with periods of remission that can last from months to years. Investigations are audiometry, electronystagmogram, vestibular evoked myogenic potentials (VEMPs) and imaging.The management consist pharmacological and non pharmacological. Meniere's disease is initially progressive but fluctuates unexpectedly. It is difficult to distinguish natural resolutions from treatment effects.